Corpora in applied linguistics - Hunston, Susan (Cambridge university press, 2002)
Corpus linguistics is leading to the development of theories about language which challenge existing orthodoxies in applied linguistics. However, there are also many questions which should be examined and debated: how big should a corpus be? Is the data from a corpus reliable? What are its applications for language teaching? This book exams these and other questions related to this emerging field. This book discusses these important issues and explores the techniques of investigating a corpus, as well as demonstrating the application of corpora in a wide variety of fields. It also outlines the impact corpus linguistics is having on how languages are taught in the classroom and how it is informing language teaching materials and dictionaries. This book makes a superb and accessible introduction to corpus linguistics and is a must read for anyone interested in corpus linguistics and its impact on applied linguistics.